The Transformational Efficacy of Postgraduate Courses - Beech, Geoffrey (Journal of research on christian education, 2019)
Considerable literature exists pertaining to transformative education and academics seek to provide a transformative educational experience for students. The purpose of this research was to examine the perceptions of graduates from postgraduate teacher education courses concerning transformative efficacy with regard to the stated outcomes of the courses. The participants were Christian teachers and school principals from Christian schools across Australia who had graduated from accredited Master of Education or Master of Education (Leadership) courses. Data collection was by way of an online survey containing Likert scales and explanatory statements. The research found that most of the graduates identified transformation at a personal level, particularly in the theological and philosophical understandings that underpin classroom or school leadership practice in Christian schools. This enabled them to be able to critique the cultural artifacts with which educators must deal in their practice.